Questions of Education and Psychology - Lavina T. A., Zakharova A. N., Gritskevich T. I., Vikhman V. V., Beketova S. I., Khaialeev A. D., Gaisin I. T., Golovachev V. S., Levashova E. A., Parshina K. V., Romanova L. N., Saltykova G. M., Severova T. S., Krasovskaia S. V., Iudin G. V., Bogatyreva L. M., Satiev R. K., Gubieva N. A., Lapshina I. V., Istomin S. V., Baklanova E. A., Stepanova O. N., Voloskov I. V., Vallis I., Barzykina T. A. (Questions of Education and Psychology, 2021)
the chapter of the monograph is devoted to the problem of implementing distance work, in particular in the cultural and educational space caused by the pandemic of a new coronavirus infection. It is noted that the abrupt transition to distance forms of work has clearly revealed the weaknesses of online education and enlightenment associated with the unavailability of the education system itself and teaching staff.
Keywords: образование; просвещение; культура; education; enlightenment; culture; дистанционная работа; distance work